Thermodynamic Signatures of Macromolecular Complexes ‒ Insights on the Stability and Interactions of Nucleoplasmin, a Nuclear Chaperone - Taneva, Stefka G.; Bañuelos, Sonia; Urbaneja, María A. (IntechOpen, 2013)
None